Citrullus colocynthis: the Most Suggested Herb in Persian Medicine for Management of Low-Back Pain - Mohamad Sanei; Roshanank Mokaberinejad*; Farzin Roozafzai; Shobeir Rostami Abousaidi (Iranian Society of Pharmacognosy, 2019)
Low-back pain is a common disease and a considerable economic burden in modern societies. Complementary and alternative therapies for assisting management of pain and disability are sought by a large number of patients. In the present work, the most common herbs used to manage Low-back pain in Iranian traditional medicine (Persian medicine) and current literature has been investigated.Chapters about low-back pain ("Vaja-e Zahr"), and radiculopathy ("Erghonnasa") and sciatica from Liber Continens (Alhavi) and Canon of Medicine were reviewed. All types of plant usage mentioned in the books including oral, rectal, and topical administration, either alone or in combination were recorded. Descriptive statistics (frequency distributions) were used to report the findings. The current literature were searched with "herbal medicine" and "low-back pain" medical subject heading (MeSH) terms in PubMed, EMBASE, ScienceDirect, Scientific Information Database (in Persian), and Google Scholar databases, to investigate medicinal usage of the most suggested plants.Citrullus colocynthis L. Schrad was the most common plant that Rhazesused in compounds and a significant herb used by Avicenna for management of low-back pain and sciatica. Fruit was the main part and rectal route was the main type of administration of colocynth for low-back pain management.In conclusion, we have proposed a new use of Citrullus colocynthis for management of low-back pain and sciatica according to the evidences from Persian medicine. According to current literature survey, no study has yet investigated or suggested the usage of Citrullus colocynthis for low-back pain management. Further laboratory and clinical studies are required to confirm the safety and efficacy of this plant or its components in low-back pain and sciatica management.